K3 surfaces and orthogonal modular forms - Clingher, Adrian; Malmendier, Andreas; Williams, Brandon (Nagoya mathematical journal, 2025)
We determine explicit generators for the ring of modular forms associated with the moduli spaces of K3 surfaces with automorphism group (Z/2Z)2(\mathbb {Z}/2\mathbb {Z})^2 and of Picard rank 13 and higher. The K3 surfaces in question carry a canonical Jacobian elliptic fibration and the modular form generators appear as coefficients in the Weierstrass-type equations describing these fibrations.
Online veröffentlicht am 29. August 2025
Gesehen am 18.02.2026